Answer:
The graph in the attached figure
Step-by-step explanation:
we have
y < -3x-2 -----> inequality A
The solution of the inequality A is the shaded area below the dashed line y=-3x-2
The slope of the dashed line is negative m=-3
The-y-intercept of the dashed line is (0,-2)
The x-intercept of the dashed line is (-0.67,0)
y > -3x+8 -----> inequality B
The solution of the inequality B is the shaded area above the dashed line y=-3x+8
The slope of the dashed line is negative m=-3
The-y-intercept of the dashed line is (0,8)
The x-intercept of the dashed line is (2.67,0)
using a graphing tool
The system of inequalities y < -3x-2 and y > -3x+8 has no solution (parallel lines)
see the attached figure
what number comes next? 80 POINTS!!
10, 3, 5, _
8, 5, 4, _
12, 6, 3, _
Answer:
7, 3 and 0
Step-by-step explanation:
10, 3, 5, 7
Because the numbers are differ by prime numbers less than 10, i.e, the difference between the numbers are 7,5 and next will be 3.
8, 5, 4, 3.
The difference between the numbers are 3, 4 and similarly it will be differ by 5 which means next will be no. 3.
12, 6, 3, 0.
The numbers are differ by 6, 9 and next will be differ by 12 resulting the next no. 0.
A cable company claims that the average household pays $78 a month for a basic cable plan, but it could differ by as much as $20. Write an absolute value inequality to determine the range of basic cable plan costs with this cable company.
Answer:
The required absolute inequality is |x - 78| ≤ 20.
Step-by-step explanation:
Consider the provided information.
Let $x is monthly charge.
The monthly charges for a basic cable plan = $78
it is given that it could differ by as much as $20
So, the maximum charges can be $78 + $20,
And, the minimum charges can be $78 - $20,
The value of x is lies from $78 - $20 to $78 + $20
Which can be written as:
78 - 20 ≤ x and x ≤ 78 + 20
-20 ≤ x - 78 and x - 78 ≤ 20
Change the sign of inequality if multiplying both side by minus.
20 ≥ -(x - 78) and x - 78 ≤ 20
⇒ |x - 78| ≤ 20
Thus, the required absolute inequality is |x - 78| ≤ 20.
A selection of staff wages is collected and shown below.
£254
£254
£310
£276
£116
£90
£312
£180
£180
£536
£350
£243
£221
£165
£239
£700
What is the mode of staff wages?
Answer:
254 and 180
Step-by-step explanation:
First of all we will define mode
"A mode is the most frequent value in the data"
In order to find mode the data is observed and the data value with most number of occurrence is called mode.
A data set can have more than one modes.
So in the given data,
The repeated data values are:
254 = two times
180 = two times
So the modes are 254 and 180 ..
Answer:
Mode of staff wages = £180
, and £254
Step-by-step explanation:
Points to remember
Mode of a data set is the most repeating item in the given data set.
To find the mode of staff wages
The given data set is,
£254, £254, £310, £276, £116, £90, £312, £180, £180, £536, £350, £243, £221, £165, £239, £700
Ascending order of data set
£90, £116, £165, £180, £180, £221, £239, £243, £254, ,£254, £276, £310, £312, £350, £536, £700
Most repeating data = £180 , and £254
Mode of staff wages = £180 , and £254
Find the slope of the line that passes through the points (-2,3) and (2,7)
Answer: 1
Step-by-step explanation:
A formula for the slope of a line is rise/run.
First let’s find the ‘rise’
To find the rise, we must look at the difference between the elevation of the points. We can find the rise by subtracting y1 from y2. 7-3=4, so the rise is 4
Run is the same concept. We must subtract x2 - x1.
2-(-2)=2+2=4
So the rise is 4 and the run is 4. There for rise/run = 4/4 =1
The slope of the line is 1
Which shows the expression x^2-1/x^2-x
Answer:
[tex]\large\boxed{\dfrac{x^2-1}{x^2-x}=\dfrac{x+1}{x}=1+\dfrac{1}{x}}[/tex]
Step-by-step explanation:
[tex]\dfrac{x^2-1}{x^2-x}=\dfrac{x^2-1^2}{x(x-1)}\qquad\text{use}\ a^2-b^2=(a-b)(a+b)\\\\=\dfrac{(x-1)(x+1)}{x(x-1)}\qquad\text{cancel}\ (x-1)\\\\=\dfrac{x+1}{x}=\dfrac{x}{x}+\dfrac{1}{x}=1+\dfrac{1}{x}[/tex]
Answer:
its b on edge 2021
Step-by-step explanation:
Simply the product (x - 4 (x + 3)
Answer:
(x - 4)(x + 3) = x² - x - 12Step-by-step explanation:
Use FOIL: (a + b)(c + d) = ac + ad + bc + bd
(x - 4)(x + 3) = (x)(x) + (x)(3) + (-4)(x) + (-4)(3)
= x² + 3x - 4x - 12 combine like terms
= x² + (3x - 4x) - 12
= x² - x - 12
Answer:
Step-by-step explanation:
You have a dangling bracket. I'm not sure what to make of it. I will solve it as
(x - 4)(x + 3) if this is not correct, could you leave me a note.
x^2 + 3x - 4x - 12
x^2 - x - 12
If you meant
(x - 4(x + 3)) then it would be solved as
x - 4x - 12 combine the xs
-3x - 12
dangling brackets are to math what dangling modifiers are to English.
Running up a tree, I saw a squirrel.
If you mean anything but that you were running up a tree, the sentence is incorrect.
find the exact value of sin 105 degrees
Answer:
[tex]\frac{\sqrt{6}+\sqrt{2}}{4}[/tex]
Step-by-step explanation:
I'm going to write 105 as a sum of numbers on the unit circle.
If I do that, I must use the sum identity for sine.
[tex]\sin(105)=\sin(60+45)[/tex]
[tex]\sin(60)\cos(45)+\sin(45)\cos(60)[/tex]
Plug in the values for sin(60),cos(45), sin(45),cos(60)
[tex]\frac{\sqrt{3}}{2}\frac{\sqrt{2}}{2}+\frac{\sqrt{2}}{2}\frac{1}{2}[/tex]
[tex]\frac{\sqrt{3}\sqrt{2}+\sqrt{2}}{4}[/tex]
[tex]\frac{\sqrt{6}+\sqrt{2}}{4}[/tex]
Sin 105 degrees is equivalent to (√6 - √2) / 4.
The exact value of sin 105 degrees can be determined using trigonometric identities. Knowing that sin (90 + θ) = cos θ, we can rewrite sin 105 degrees as sin (90 + 15) degrees.
Applying the identity, sin (90 + 15) degrees equals cos 15 degrees.
Utilizing the trigonometric values of common angles, cos 15 degrees can be expressed as (√6 - √2) / 4.
This value is derived from trigonometric relationships, providing an exact representation of sin 105 degrees without resorting to decimal approximations.
Which of the following are solutions to the equation below? Check all that apply (2x+3)^2=10
Answer:
Option C and E are correct.
Step-by-step explanation:
We need to solve the following equation
(2x+3)^2=10
taking square root on both sides
[tex]\sqrt{(2x+3)^2}=\sqrt{10}\\2x+3=\pm\sqrt{10}[/tex]
Now solving:
[tex]2x+3=\sqrt{10} \,\,and\,\,2x+3=-\sqrt{10}\\2x=\sqrt{10}-3 \,\,and\,\,2x=-\sqrt{10}-3\\x=\frac{ \sqrt{10}-3}{2} \,\,and\,\,x=\frac{-\sqrt{10}-3}{2}[/tex]
So, Option C and E are correct.
Answer: E .√10 - 3 / 2 or
c. -√10 - 3 / 2
Step-by-step explanation:
(2x + 3)^2 = 10
take the square root of bothside
√(2x + 3)^2 = ±√10
2x + 3 = ±√10
subtract 3 from bothside
2x = ±√10 - 3
Divide bothside by 2
x = ±√10 - 3 / 2
Either x = √10 - 3 / 2 or
x = -√10 - 3 / 2
Could you guys plesssse help me with 3
and 4
Look at the figure, . Find the values of x and y. x = 5, y = 7 x = 6, y = 8 x = 6, y = 9 x = 7, y = 10
Answer:
x = 6, y = 9
Step-by-step explanation:
One of the properties of a parallelogram is
The diagonals bisect each other, hence
2x = y + 3 → (1)
2y = 3x → (2)
Rearrange (1) in terms of y by subtracting 3 from both sides
y = 2x - 3 → (3)
Substitute y = 2x - 3 into (2)
2(2x - 3) = 3x ← distribute left side
4x - 6 = 3x ( add 6 to both sides )
4x = 3x + 6 ( subtract 3x from both sides )
x = 6
Substitute x = 6 into (3) for value of y
y = (2 × 6) - 3 = 12 - 3 = 9
Hence x = 6 and y = 9
if X parallel Y and Y parallel Z then
Answer:
X || Z
Step-by-step explanation:
We are not told about any lines being perpendicular, so we cannot conclude any lines to be perpendicular.
Theorem:
If two lines are parallel to the same line, then the two lines are parallel to each other.
X is paralle to Y; Z is parallel to Y.
Line X and Z are parallel to the same line, Y, so lines X and Z are parallel.
Answer: X || Z
In mathematics, if lines X and Y are parallel, and lines Y and Z are parallel, then lines X and Z are also parallel. This is known as the transitive property.
Explanation:In mathematics, when we say one line is parallel to another, we mean they are moving in the same direction and they will never intersect. In the case of X being parallel to Y and Y being parallel to Z, according to the transitive property in mathematics, it follows that X would be parallel to Z. To visualize this, imagine three straight lines on a piece of paper. If Line X and Line Y never meet and continue in the same direction, and Line Y and Line Z also follow the same rule, then logically, Line X and Line Z must also be continuing in the same direction and never intersecting, hence they are essentially parallel to each other.
Learn more about Parallel Lines here:https://brainly.com/question/32035102
#SPJ2
Calculate 2.6 x 10 times 4.5 x 108 by using scientific notation and the product rule.
Express your answer in scientific notation with the proper number of significant figures.
Answer:
[tex]1.17*10^{10}[/tex]
Step-by-step explanation:
wee know that
To multiply two numbers in scientific notation, multiply their coefficients and add their exponents
In this problem we have
[tex](2.6*10^{1})*(4.5*10^{8})=(2.6*4.5)*10^{1+8}=11.7*10^{9}=1.17*10^{10}[/tex]
A thief steals an atm card and must randomly guess the correct three digit pin code from a 9 key keypad repetition of digits is allowed. That is the probability of a correct guess in the first try?
The probability of guessing a 3-digit pin correctly on the first attempt, when repetition of digits is allowed, is 1 out of 1000, or 0.001.
Explanation:The subject under scrutiny is related to the concept of probability in mathematics. To solve this, we need to consider that there are 10 possible digits (0 to 9) on the keypad for each of the 3 input spots in the pin. Since a digit can be repeated, each spot has 10 possibilities. The total number of possible pin combinations is thus 10*10*10 = 1000.
The probability of guessing the pin correctly on the first attempt would be 1 (since there's only one correct pin) divided by the total number of possibilities, which is 1000. Therefore, the probability of this happening is 1/1000 or 0.001.
Learn more about probability here:https://brainly.com/question/32117953
#SPJ12
The probability of a correct guess on the first try is 1/729.
Explanation:In this scenario, the thief must randomly guess the correct three-digit pin code from a 9-key keypad where repetition of digits is allowed. To determine the probability of a correct guess on the first try, we need to calculate the ratio of favorable outcomes to total outcomes.
There are 9 possible digits to choose from, and repetition is allowed. Therefore, the number of outcomes is 9 raised to the power of 3 (since the thief needs to guess a three-digit pin code). This gives us 729 total outcomes. There is only one favorable outcome in this case, which is the correct pin code. Therefore, the probability of a correct guess on the first try is 1/729.
Learn more about Probability here:https://brainly.com/question/32117953
#SPJ12
Question 7!!!! 12 points
Answer:
[tex]35+50x\le 1325[/tex]
Step-by-step explanation:
So y=mx+b tells us the initial amount is b (also known as the y-intercept).
Anyways you have to pay a one time fee of 35 dollars and then it is 50 dollars per month.
Let x represent the number of months she goes to yoga.
If she goes 1 month it costs her 35+50.
If she goes 2 months it costs her 35+50+50 or just 35+50(2).
If she goes 3 months it costs her 35+50+50+50 or just 35+50(3).
If she goes x months it costs her 35+50x.
Now she only has 1325.
So we want the cost of her x months to be less than or equal to 1325 because she doesn't have more than that.
So we want [tex]35+50x\le 1325[/tex]
Answer:
C
Step-by-step explanation:
Since she want to use her savings of $1325 it means that that is all the money Abbey is going to use so it means that the $1325 is greater or equal to the money she can or is going to spend. There is a one time fee of $35 which is going to be added to it and a monthly fee of $50. Since you don't know how many months, it'll be replaced with an x. so the equation will be 35+50x≤$1325
Simplify 5(x - 2) - 3x + 7.
5(x - 2) - 3x + 7.
First use the distributive property:
5(x-2) = 5x-10
Now you have:
5x - 10 - 3x +7
Now combine like terms to get:
2x - 3
Answer:
2x -3
Step-by-step explanation:
5(x - 2) - 3x + 7
Distribute the 5
5x -10 -3x+7
Combine like terms
5x-3x -10 +7
2x -3
Factor completely
3x^2+2x-1
Answer:
[tex]3x^2 + 2x - 1 = 3(x-\frac{1}{3})(x+1)[/tex]
Step-by-step explanation:
Answer:
(3x-1)(x+1)
Step-by-step explanation:
I like to factor by grouping.
a=3
b=2
c=-1
To get those values I compared 3x^2+2x-1 to ax^2+bx+c.
Now our objective to help us factor this is: Find two integers that multiply to be a*c and add up to be b.
a*c=3(-1)
b=2
Guess what? Our numbers are already visible to us; that doesn't always happen. However, a*c=3(-1) and b=2=3+(-1).
So we are going to replace our 2x with 3x+-1x or -1x+3x. Either one is fine; they are the same thing.
3x^2+2x-1
Replacing 2x with -1x+3x.
3x^2-1x+3x-1
Grouping first 2 terms together and grouping 2nd 2 terms together.
(3x^2-1x)+(3x-1)
Now we are going to factor each grouping.
x(3x-1)+1(3x-1)
Now notice we have two terms here x(3x-1) and 1(3x-1). Both of these terms have a common factor of (3x-1). We are going to now factor out (3x-1).
(3x-1)(x+1)
what is the range of the function on the graph?
a. all real numbers
b. all real numbers greater than or equal to 0
c. all real numbers greater than or equal to 1
d. all real numbers greater than or equal to 2
Answer:
the answer is D. all real numbers greater than or equal to 2.
Step-by-step explanation:
looking at the graph, half of a parabola is curved upwards, and will never stop going up. looking at (1, 2), the dot (instead of circle) indicates the range is greater than or equal to itself, which is 2.
Option: d is the correct answer.
d. all real numbers greater than or equal to 2
Step-by-step explanation:Domain of a function--
The domain of the function is the set or collection of all the x-values for which the function is well defined.
Range of a function--
The range of a function is the set of all the values which are attained by a function in it's defined domain.
By looking at the graph we observe that the function is continuously increasing and the function takes all the real values greater than as well as equal to 2( since there is a closed circle at (1,2) )
Hence, the range is: [2,∞)
An ellipse has a vertex at (5,0), a co-vertex at (0, -3), and a center at the origin. Which is the equation of the ellipse in standard form?
Answer:
[tex]\frac{x^2}{25}+\frac{y^2}{9}=1[/tex]
Step-by-step explanation:
[tex]\frac{(x-h)^2}{a^2}+\frac[(y-k)^2}{b^2}=1[/tex]
her center [tex](h,k)[/tex], and [tex]a[/tex] is the horizontal radius, and [tex]b[/tex] is the vertical radius.
So the center is [tex](h,k)=(0,0)[/tex].
[tex]a=5[/tex] because (5,0) has a distance of 5 from (0,0).
[tex]b=3[/tex] because (0,-3) has a distance of 3 from (0,0).
So the equation is:
[tex]\frac{(x-0)^2}{5^2}+\frac{(y-0)^2}{3^2}=1[/tex]
Simplifying a bit:
[tex]\frac{x^2}{25}+\frac{y^2}{9}=1[/tex]
Final answer:
The equation of the ellipse with a vertex at (5,0) and a co-vertex at (0, -3) with the center at the origin is [tex]\(\frac{x^2}{25} + \frac{y^2}{9} = 1\).[/tex]
Explanation:
The equation of an ellipse in standard form with a center at the origin can be derived from its vertices and co-vertices. For an ellipse centered at the origin, the standard form of the equation is [tex]\(\frac{x^2}{a^2} + \frac{y^2}{b^2} = 1\)[/tex], where a is the semi-major axis and b is the semi-minor axis. Given that one vertex is at (5,0), we can deduce that the semi-major axis a is 5. Since a co-vertex is at (0, -3), the semi-minor axis b is 3. Thus, the equation of the ellipse in standard form is [tex]\(\frac{x^2}{5^2} + \frac{y^2}{3^2} = 1\), or \(\frac{x^2}{25} + \frac{y^2}{9} = 1\).[/tex]
What is the volume of a room that is 13 feet by 9 feet by 11 feet? A. 1300 cubic feet B. 1207 cubic feet C. 1287 cubic feet D. 1200 cubic feet
Answer:
C) 1287 cubic feet
Step-by-step explanation:
To find the volume of a rectangular prism the formula is length time width times height. That means area=9*11*13 which is 1287 or C.
Find the sum of (-4+ i) and (10 - 51).
-3+ 51
-3-51
06-41
6-61
DONE
Answer:
The correct answer is 6-4i
Answer:
6 - 4i .
Step-by-step explanation:
I will assume that (10 - 51) is ( 10 - 5i) since the other number is a complex number.
You add the real parts and the imaginary parts separately.
(-4 + i) + (10 - 5i)
= (-4 + 10) + (i - 5i)
= 6 - 4i .
In parallelogram math, angle m = (3x+20) and angle T = (5x-4). Find angle A
Answer:
M=T = angle A
try it
then. find angle a the sum of palleogram is .... then 12+A=....
angle A=........
help me to do this question friends
Answer:
First draw two axes x and y. Then mark all points for which x=4, this is a vertical line. Do the same for the other sides and you will find a square with side length 8.
If 111 people attend a concert and tickets for adults cost $4 while tickets for children cost $3.25 and total receipts for the concert was $401.25, how many of each went to the concert?
Answer:
57 children
54 adults
Step-by-step explanation:
Let's call x the number of children admitted and call z the number of adults admitted.
Then we know that:
[tex]x + z = 111[/tex]
We also know that:
[tex]3.25x + 4z = 401.25[/tex]
We want to find the value of x and z. Then we solve the system of equations:
-Multiplay the first equation by -4 and add it to the second equation:
[tex]-4x - 4z = -444[/tex]
[tex]3.25x + 4z = 401.25[/tex]
----------------------------------
[tex]-0.75x = -42.75[/tex]
[tex]x =\frac{-42.75}{-0.75}\\\\x=57[/tex]
Now we substitute the value of x in the first equation and solve for the variable z
[tex]57 + z = 111[/tex]
[tex]z = 111-57[/tex]
[tex]z = 54[/tex]
Answer:
Number of children=57
Number of adults=54
Step-by-step explanation:
We can start by forming simultaneous equations from the information provided.
Let the number of children be x and adults be y, then the the sum of the amount collected from both children and adults=3.25x+4y=401.25
The total number of people in attendance x+y=111
Let us solve these equations simultaneously.
3.25x+4y=401.25
x+y=111
Using substitution method.
y=111-x
3.25x+4(111-x)=401.25
3.25x+444-4x=401.25
-0.75cx=-42.75
x=57
Number of children=57
Adults=111-57
=54
A vessel has 13 liters 200 ml of fruit juice. in how many glass of each capacity 60 milliliters can be filled
Answer:
220 glasses.
Step-by-step explanation:
Quantity of fruit juice = 13 liters 200 ml
Number of glasses of each capacilty 60ml can be filled = ?
The quantity of fruit juice has 2 units. one is liter and the other is milliliter.
So we will convert liter into milliliter.
We have the quantity 13 liters 200 ml:
We know that:
1 liter = 1000 ml
Hence we have 13 liters so 13 will be multiplied by 1000 to convert it into milliliter.
13 * 1000 = 13000 ml
Now we have 13000 ml 200ml
Notice that we have two milliliters, so we will add both the quantities to make it one.
(13000+200)ml = 13200ml
Total quantity of fruit juice = 13200ml
Now divide the total quantity by the capacity of 60ml
=13200ml/60ml
= 220 glasses
It means that 220 glasses can be filled....
The length of a spring varies directly with the mass of an object that is attached to it. When a 30 gram object is attached the spring stretches 9 centimeters. Which equation relates the mass of and object, m, and the length of a spring s.
A s= 3/10m
B s= 10/3m
C m= 3/10s
D m=10/3s
Answer:
A. s = 3/10 m.
Step-by-step explanation:
s = km where k is a constant , s = the length of the string and m = the mass of the object.
Substituting m = 30 and s = 9:
9 = k * 30
k = 9/30 = 3/10
So the equation is s = 3/10 m.
After returning from a holiday to the USA, Megan has some American coins: A 25c coins and B 10c coins with a total value of $1.95, where A and B are both counting numbers. how many different values of A can Megan have?
Megan can have 7 different values of A for the number of 25c coins she possesses.
Given:
Megan has 25c coins and 10c coins with a total value of $1.95.
To find:
Number of different values of A (number of 25c coins) Megan can have.
Step-by-step solution:
Let A represent the number of 25c coins and B represent the number of 10c coins.From the given information, we can form the equation 25A + 10B = 195 (since the total value is $1.95).We know A and B are counting numbers (positive integers).Now, find the possible values of A that satisfy the equation and the conditions: A = 1, 2, 3, 4, 5, 6, 7.Therefore, Megan can have 7 different values of A for the number of 25c coins she possesses.
9x2+4y2 = 36 The foci are located at:
Answer:
The foci are located at [tex](0,\pm \sqrt{5})[/tex]
Step-by-step explanation:
The standard equation of an ellipse with a vertical major axis is [tex]\frac{x^2}{b^2}+\frac{y^2}{a^2}=1[/tex] where [tex]a^2\:>\:b^2[/tex].
The given equation is [tex]9x^2+4y^2=36[/tex].
To obtain the standard form, we must divide through by 36.
[tex]\frac{9x^2}{36}+\frac{4y^2}{36}=\frac{36}{36}[/tex]
We simplify by canceling out the common factors to obtain;
[tex]\frac{x^2}{4} +\frac{y^2}{9}=1[/tex]
By comparing this equation to
[tex]\frac{x^2}{b^2}+\frac{y^2}{a^2}=1[/tex]
We have [tex]a^2=9,b^2=4[/tex].
To find the foci, we use the relation: [tex]a^2-b^2=c^2[/tex]
This implies that:
[tex]9-4=c^2[/tex]
[tex]c^2=5[/tex]
[tex]c=\pm\sqrt{5}[/tex]
The foci are located at [tex](0,\pm c)[/tex]
Therefore the foci are [tex](0,\pm \sqrt{5})[/tex]
Or
[tex](0,-\sqrt{5})[/tex] and [tex](0,\sqrt{5})[/tex]
Simply the imaginary number square root -45
Answer:
3i[tex]\sqrt{5}[/tex]
Step-by-step explanation:
Using the rule of radicals
[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]
and [tex]\sqrt{-1}[/tex] = i
Given
[tex]\sqrt{-45}[/tex]
= [tex]\sqrt{9(5)(-1)}[/tex]
= [tex]\sqrt{9}[/tex] × [tex]\sqrt{5}[/tex] × [tex]\sqrt{-1}[/tex]
= 3 × [tex]\sqrt{5}[/tex] × i
= 3i[tex]\sqrt{5}[/tex]
what is the sum of 6x3+8x2-2x+4 and 10x3+x2+11x+9
Answer:
16x³ + 9x² + 9x + 13
Step-by-step explanation:
Given
6x³ + 8x² - 2x + 4 and 10x³ + x² + 11x + 9
Sum the 2 expressions by adding like terms, that is
= (6x³ + 10x³) + (8x² + x²) + (- 2x + 11x) + (4 + 9)
= 16x³ + 9x² + 9x + 13
Can you use the ASA Postulate or the AAS Theorem to prove the triangles congruent? (1)
Answer:
asa only because the two triangles are facing each other like a reflection making them congruent
ΔWZV and ΔWZY are congruent by AAS congruency
What is congruency?Congruent triangles are triangles having both the same shape and the same size.Types of congruencies are SSS, SAS, AAS, ASA, RHS.How to prove that the triangles are congruent?In the given figure there are two triangles, ΔWZV and ΔWZYConsidering ΔWZV and ΔWZY
∠WVZ = ∠WYZ (given)
∠WZV = ∠WZY ( both angles are 90° since it is given that WZ is perpendicular to VY)
WZ is common side
So ΔWZV and ΔWZY are congruent (AAS congruency)
Find more about "Congruency" here: https://brainly.com/question/2938476
#SPJ2